Effects of dietary bacterial phytase on growth, nutrient and phosphorus utilization of tilapia (Oreochromis spp.) - Dechavez, Rande Babac (University of the Philippines Visayas, 2012)
Results of study 1 show that phytases from Bacillus namely B. pumilus, B. megaterium, B. coagulans, and B. licheniformis were characterized. All strains investigate were able to hydrolyze extracellular phytate. The activity of phytase increased markedly in late stationary phase in all the species tested. The highest enzyme activity was found in B. megateriumphytase after the 4th day of culture. The crude phytases from the different Bacillus strains were optimally active at pH values from 5.5 to 7.0 at 370C and retained activity at assay temperatures up to 800C. The enzymes exhibited some degrees of thermostability, retaining ~50% activity of 700C and werefairly stable up to pH 10. These properties indicated that the Bacillus phytases could be suitable for animal feed supplementation in aquaculture to improve availability of phosphorous (P). B. pumilus, B. megaterium, and B. licheniformes exhibited the highest phytase activity on cassava leaf meal, soybean meal and corn meal, respectively. The apparent digestibility coefficient (ADC%) of feeds ranged from 86.3 to 88.3%. Fish fed diets supplemented with B. megateriumphytase exhibited the highest ADC. Study 2 aims to determine the effects of different bacterial phytases from Bacillus spp. supplemented to tilapia diet on growth, feed utilization and nutrient deposition of tilapia mossambica fingerlings under laboratory conditions for 60 days. Diets were supplemented with 500 FTU kg-1 of B. pumilus, B. megaterium and B. licheniformisphytases while diet without supplementation and the commercial diet served as negative and positive controls, respectively. Results of the study showed that growth of fish fed diets containing bacterial phytases was superior to those of the negative and commercial diets, although no significant differences were observed. Fish fed diets supplemented with B. megateriumphytase displayed the highest FCE, PER and protein retention than did fish fed the other diets. Fsh fed diets containing different bacterial phytases exhibited higher ash, P, Ca and Mg concentrations in scales, bone and vertebrae than those fish fed diets without supplementation and the commercial diet. Fecal P concentrations were lower in fish fed the supplemented diets which could consequently reduce the estimated excretion of P effluent by 36% and 29% compared to fish fed diets without supplementation. Phytase from B. megaterium was the most effective in improving bioavailability of phytate P in sex reversal tilapia and may possibly reduce or eliminating the use of P1 supplementation in their diets.